Safety and efficacy of a fixed dose combination of oral drops of paracetamol, phenylephrine hydrochloride, and chlorpheniramine maleate in the symptomatic treatment of common cold in children: an active post-marketing surveillance study - Dewan, Bhupesh; Shinde, Siddheshwar; Motwani , Nisha (International Journal of Contemporary Pediatrics, 2024)
Background: Common cold often accompanied by mild fever and systemic symptoms in children, poses a significant social burden. Scientific evidence suggests that the pathogenesis of colds involves the activation of multiple inflammatory pathways, rendering single-molecule treatment ineffective against the symptoms. This active post-marketing surveillance study evaluated the safety and efficacy of a fixed-dose combination containing paracetamol, phenylephrine hydrochloride, and chlorpheniramine malate in treating common cold in children aged 2 to 5 years. Methods: In this clinical study, 200 children with common cold symptoms were enrolled. Maxtra® P oral drops, a fixed-dose combination containing paracetamol (125 mg), phenylephrine hydrochloride (2.5 mg), and chlorpheniramine maleate (1 mg) per ml drops, were administered as 1 ml every 4 to 6 hours for 5 days. Safety was assessed using the global tolerability assessment based on responses from parents and investigators. Efficacy was evaluated based on symptom severity scores categorised as absent, mild, moderate, severe, or very severe. Results: Complete remission from common cold symptoms was achieved in 82% (164 patients) of 200 patients. Statistically significant reductions (p<0.001) in symptom severity scores were observed for all common cold symptoms from day 1 to day 5. No adverse events were observed. Maxtra® P oral drops were regarded as good to excellent for treating common cold symptoms by 92.5% of parents and 97.5% of investigators. Conclusions: The observations of study indicate that Maxtra® P oral drops are efficacious and well- tolerated for treating common cold in children aged 2 to 5 years.